2012
DOI: 10.1007/s11748-012-0139-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular surgery for realization of regenerative medicine

Abstract: Regenerative medicine is emerging as a new approach to the treatment of severe cardiovascular diseases that are resistant to conventional therapies. Although the type of cell transplanted (e.g., pluripotent stem cells, bone marrow-derived stem cells, skeletal myoblasts, or cardiac stem cells) influences the outcome of stem cell transplantation, the method of transplantation is also important, as the efficiency of engraftment after simple needle injection is poor. Scaffold-free cell sheet transplantation techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 98 publications
0
14
0
Order By: Relevance
“…26 MSCs are considered an attractive cell source for regenerative medicine because of their excellent capacity for proliferation and differentiation. [27][28][29] A considerable number of clinical trials using MSCs have been conducted targeting various disorders, including acute myocardial infarction, 30 ischemic heart failure, 31,32 graft versus host disease, 33 inflammatory bowel disease, 34 and respiratory disease. 35 Several studies that have used experimental animal models of lung injury induced by lipopolysaccharides, 7 bleomycin, 36 artificial ventilation, 9 and hemorrhage shock 8 generally have demonstrated that MSCs attenuate the production of inflammatory cytokines and reduce edema and neutrophil recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…26 MSCs are considered an attractive cell source for regenerative medicine because of their excellent capacity for proliferation and differentiation. [27][28][29] A considerable number of clinical trials using MSCs have been conducted targeting various disorders, including acute myocardial infarction, 30 ischemic heart failure, 31,32 graft versus host disease, 33 inflammatory bowel disease, 34 and respiratory disease. 35 Several studies that have used experimental animal models of lung injury induced by lipopolysaccharides, 7 bleomycin, 36 artificial ventilation, 9 and hemorrhage shock 8 generally have demonstrated that MSCs attenuate the production of inflammatory cytokines and reduce edema and neutrophil recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…15 We have previously reported the effectiveness of the biodegradable glue as a novel surgical sealant for lung air leakage 14 or an attachment medium for sustained release of antibiotics or antiarrhythmic drugs in experimental animal models. [16][17][18] The purpose of this study is to examine the effect of the biodegradable glue on retrosternal adhesion and, using a rabbit pericardiectomy model, to evaluate the inflammatory and fibrogenic capacity and biocompatibility of the glue for wide clinical application of this new material in cardiac surgery.…”
mentioning
confidence: 99%
“…HiPSCs are now one of the most promising cell sources for cardiac regenerative cell therapy [54][55][56]. There are major methods of cell delivery, including intracoronary or intramuscular injection of dispersed cells and epicardial transplantation of engineered tissues [57].…”
Section: Transplantation Therapymentioning
confidence: 99%